Psychosis. Issue 3 (June 2018) - Schrimpf, Lindsey A.; Aggarwal, Arpit; Lauriello, John
ABSTRACT: PURPOSE OF REVIEW: Psychosis is a psychiatric condition that has significant overlap with neurologic disease. This article is intended to educate the neurologist on the psychiatric manifestations of psychosis and its evaluation, diagnosis, and treatment. How to differentiate a primary psychiatric cause of psychosis from psychosis secondary to a medical or neurologic condition is also reviewed. RECENT FINDINGS: Current research in psychotic disorders has focused increasingly on negative symptoms and cognitive impairment in psychotic illness, as it is now recognized that these cause the greatest impact on functional deficits for patients. A number of new medications have also been introduced to target negative symptoms and cognitive deficits in psychotic illness. These have new implications in terms of treatment overlap with medications being prescribed by providers in psychiatry, neurology, and general practice. SUMMARY: This article discusses the current methods for evaluating, diagnosing, and treating psychosis. Psychosis as a primary mental health disorder is a diagnosis of exclusion, as psychosis can be a direct symptom of underlying medical or neurologic disease. Delirium and dementia are the two most important disorders to rule out. This article will help readers be more prepared to assess and treat the patient with psychosis.